(?-p-Cymene)bis-(trichlorido-stannyl)(triethoxy-phosphine-?P)ruthenium(II) - Shapovalov, Sergey S.; Therrien, Bruno (My University, 2009)
In the title complex, [RuSn(2)(C(10)H(14))Cl(6)(C(6)H(15)O(3)P)], the Ru-Sn bond lengths [2.5619 (3) and 2.5669 (3) Å] are about 0.3 Å shorter than the sum of the covalent Ru and Sn radii (1.46 + 1.39 = 2.85 Å), in line with other structurally characterized arene ruthenium trichlorido-stannyl derivatives. The Ru(II) atom is surrounded by a para-cymene, a triethylphosphite and two trichloridostannyl ligands in a typical piano-stool coordination.[on SciFinder (R)]